Empirical analysis of the best warehousing practices and its impact on cocoa beans quality: the perspective of cocoa producers (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2020)
The importance of cocoa to the economy of Ghana cannot be overemphasized. For several  decades, cocoa has been the backbone of the country's economy and plays a major role in employment, foreign exchange earnings, government revenue, education, and infrastractural development of  Ghana. Ghana is the world premier supplier of high quality cocoa and second largest exporter of the commodity. Maintaining this high quality of cocoa beans is important if Ghana is to maintain this status, and in so doing, continue charging a premium price for its cocoa. In this study, four best practices of cocoa warehousing were identified from literature and the impact they have on the quality of cocoa beans was explored in mach detail using data collected from sixty-six district managers and depot keepers of cocoa warehouses in the Agona East and Agona West districts of the Central region of Ghana. A structural equation model was developed and tested to explore this phenomenon and the findings revealed that the four cocoa warehousing best practices - inventory control, warehouse maintainance, warehouse inspection, and records keeping- were significantly positively associated with the quality of cocoa beans. This suggests that all efforts aimed at improving these aspects of cocoa warehousing  would  reflect positively on the quality  of cocoa beans. The study also revealed important challenges to cocoa warehousing in the sampled cocoa warehouses and depots including low capacity of warehouses, poor lighting, poor ventilation, attack by pest and diseases, mishandling, insufficient equipments and facilities, pilferage and damage of cocoa beans, and lack of training for staff and other workers of cocoa warehousing and storage institutions. These challenges threaten to lower the quality of Ghana's cocoa beans. The study recommends  that greater investment should be channelled into cocoa warehousing as doing so would address most of the challenges identified. The study also calls for further research into other cocoa warehousing practices not tackled in this study to determine how they impact on the quality of cocoa bean.